2021
DOI: 10.3389/fendo.2021.608697
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Myo-Inositol and Selenium Contrasts Cadmium-Induced Thyroid C Cell Hyperplasia and Hypertrophy in Mice

Abstract: Previous studies have demonstrated that, in addition to inducing structural changes in thyroid follicles, cadmium (Cd) increased the number of C cells. We examined the effects of myo-inositol (MI), seleno-L-methionine (Se), MI + Se, and resveratrol on C cells of mice exposed to cadmium chloride (Cd Cl2), as no data are currently available on the possible protective effects of these molecules. In contrast, we have previously shown this protective effect against CdCl2 on the thyroid follicles of mice. Ninety-eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Extracellular domains of the integrins, a known family of transmembrane glycoproteins, interact with a variety of ligands (35), including extracellular matrix glycoproteins, and the intracellular domain linked to the cytoskeleton (36). Moreover, it has been demonstrated that the thyroid hormone could influence the interaction of integrins with the extracellular matrix protein (22). At this purpose, αvβ3-integrin has a large number of extracellular protein ligands, including growth factors and extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular domains of the integrins, a known family of transmembrane glycoproteins, interact with a variety of ligands (35), including extracellular matrix glycoproteins, and the intracellular domain linked to the cytoskeleton (36). Moreover, it has been demonstrated that the thyroid hormone could influence the interaction of integrins with the extracellular matrix protein (22). At this purpose, αvβ3-integrin has a large number of extracellular protein ligands, including growth factors and extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous results in epithelial and glandular tissues, in the present report we performed a study on SGs and integrins in thyrocytes. In particular, we studied all SGs and the αvβ3-integrin, a cell surface receptor for thyroid hormone, which is the initiation site for T4-induced activation of intracellular signalling cascades (21) by activation of the sodium pump (14,22). As this integrin is also widely present on cancer cells, it was clear that the thyroid hormone has also been found to cause proliferation of a variety of human cancer lines via the cell surface receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) is listed as one of 126 priority pollutants and a kind of carcinogen. There are insufficient studies on its effects on the thyroid, but it has been reported that chronic Cd poisoning is common in cases of colloid cystic goiter, adenomatous follicular hyperplasia with low dysplasia and reduced Tg secretion, and diffuse nodular hyperplasia and hypertrophy of parafollicular cells ( 132 – 134 ).…”
Section: Introductionmentioning
confidence: 99%